IMPACT OF SATISFACTION AND SWITCHING COST ON LOYALTY (CASE STUDY : CUSTOMER OF SIMPATI PROVIDER IN SURABAYA) - Yessy Artanti; Diani Marischawati (Jurnal Ilmiah Ekonomi Bisnis, 2012)
Cellular services industry in Indonesia is currently located in the saturated, inwhich development can’t run as fast as before, even to decline. In times ofsaturated, if the market penetration can’t produce high profits, keeping thecustomer loyalty is one of the best ways for company to gain profit. The way tomaintain customer loyalty is to satisfy customers. But, in the hypercompetitif era,not only customer satisfaction is needed to maintain customer loyalty. Severalcompanies are also implementing the same customer satisfaction strategy, socustomers have a great power to move. To anticipate the movement of customers,it is necessary to apply another strategy. Biaya peralihan which are costs to beborne by the customer if the customer decides to switch, also serves to maintaincustomer loyalty. One of the biaya peralihan strategies adopted by Telkomsel tomaintain the customers loyalty is to making “simPATIzone” community for it’scustomer. Therefore the study aims are to examine and analyze the impact ofcustomer satisfaction on customer loyalty with biaya peralihan as a moderatorvariable on the simPATI phone card customers (studies on “simPATIzone”community In The WTC’s Surabaya). This study is a causal research. Thepopulation in this study is age 16-65 years, do not have other brands of GSMcard, and have been using phone cards simPATI for at least 1 year. Samplescollected as many as 210 respondents using accidental sampling technique.Measuring instrument used was a questionnaire, and data were analyzed withModerate Regression Analysis (MRA). The results showed that biaya peralihanbe a moderate variable is weakened the impact of customer satisfaction tocustomer loyalty. The result of regression, estimate adjusted R2 on 0,969 and thisaimed 96,9% changes of customer loyalty is depends of customer satisfaction,biaya peralihan, and interaction variable, and the other of variable aimed 3,1%.Suggested for other examined, to making biaya peralihan be second independentvariable in order not weakened the impact of customer satisfaction to customerloyalty.Key Words: customer satisfaction, biaya peralihan, customer loyalty